SUPERVISED INTERNSHIP IN EDUCATIONAL MANAGEMENT AND TEACHING APPRENTICESHIP: CONTRIBUTIONS TO THE TRAINING OF THE EDUCATIONAL PROFESSIONALS - Daros Parente, Claudia da Mota [UNESP]; Santos de Jesus, Carla Mayara dos [UNESP]; Nascimento, Elaine Valeria do [UNESP]; Fidalgo e Silva, Jaqueline Lima [UNESP] (Fundacao Univ Tocantins, 2021)
This article aims to report an experience that connected the Supervised Internship of Educational Management in the Pedagogy Course to the Teaching Apprenticeship of the Postgraduate in Education. The training of teachers-managers-researchers was based on the principles of research-proposition, in addition to highlighting the importance of the relations between theory and practice and the dialogue between institutions and professionals in basic education and higher education. The report privileged three thematic aspects that show the connections of the developed internships: 1) management of education systems and school management; 2) challenges of democratic school management; 3) the pedagogical coordinator's work. The experience resulted in benefits for institutions and subjects involved in the internships, as it provided moments and spaces for training and reflections on professional experiences and practices.
Keywords: Teacher Training; Supervised internship; Teaching apprenticeship; Educational management